Strategi Komunikasi Pemasaran Penyelengaraan Event Dan Festival Pariwisata Di Kabupaten Banyuwangi - Amalliah; Katry Anggraini (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2023)
Banyuwangi Festival 2022, is a cultural arts event in Banyuwangi district, it is hoped that holding the event for one year can have a multiplier effect for the people of Banyuwangi. An integrated communication strategy or Integrated marketing communication in promoting tourism in the Banyuwangi area is determined by the Banyuwangi Tourism Office in the advertising and event categories. By using qualitative research methods to describe an integrated marketing strategy for the Banyuwangi Festival in 2022, the Banyuwangi Regency Tourism Office is optimistic about development efforts and efforts to increase the number of tourist visitors, both local and foreign. Therefore, this marketing strategy can be a strategic management tool to ensure the right type of consumers, namely pro-sustainable tourists, who come to tourist sites, and to consider destination capacity and visit management. Therefore, this marketing strategy can be a strategic management tool to ensure the right type of consumers, namely pro-sustainable tourists, who come to tourist sites, and to consider destination capacity and visit management. .